Addressing sexual violence on campus - Monkhe, Palesa Kenuwe (Rhodes University, 2025)
This research explored how first-year men students at a South African university construct sexual violence using Foucauldian Discourse Analysis. Through the use of vignettes depicting various sexual encounters, the study examined participants’ interpretations of these scenarios and the underlying discourses about sexual violence that emerged in their talk. Five key discourses were identified: Sexual Refusal, Justification, Responsibility, Trauma and Damage, as well as the discourse of ‘real’ Rape. Participants’ interpretations informed these discourses of sexual violence as involving the absence of consent, the presence of physical force, exploitation of vulnerability, trauma, and sexual violence as a criminal/moral wrongdoing. The findings reveal that participants’ discourses largely aligned with existing societal narratives about SV and sex, often reflecting and reproducing harmful societal perspectives about gender, sex and interpersonal relations. While some participants showed progressive narratives and positions of compassion, uncritical engagement with these discourses perpetuated understandings that normalise unequal power dynamics in sexual relations. Participants’ talk illustrated varying levels of readiness to intervene in sexual violence scenarios, taking active respondent positions in some scenarios while showing uncertainty in others. Their negotiated interpretations of the vignettes suggest a potential for influential roles in challenging harmful campus cultures around sexual violence.
an exploration of first-year university men’s constructions of sexual violence through a Foucauldian discourse analysis
Keywords: Sexual consent (http://id.loc.gov/authorities/subjects/sh98003848); Rape culture (http://id.loc.gov/authorities/subjects/sh2019103596); Male college students (http://id.loc.gov/authorities/subjects/sh95000038); Masculinity (http://id.loc.gov/authorities/subjects/sh85081797); Pscyhology; Sexual violence (https://www.wikidata.org/wiki/Q558075); Foucauldian discourse analysis (https://www.wikidata.org/wiki/Q8564954)